TIKTOK AS A LEARNING MEDIUM IN TEACHING SPEAKING SKILL: : EFL STUDENTS’ PERCEPTION - Farisa Rahma Yulita; Hertiki Hertiki (Journey: Journal of English Language and Pedagogy, 2023)
This study intended to investigate how students feel about utilizing TikTok as a learning tool to develop their speaking abilities. Social media is crucial to modern living, especially advancing education in the digital age. TikTok, one of the most popular social media platforms, is presently thought to be able to help students with their speaking abilities. The data from this research were statements from interview sessions conducted by five students in 11th grade at SMA Sejahtera Surabaya as a data source. The results obtained from this study were 3 different perceptions held by students. First, TikTok can be utilized as an extra learning tool because it offers a wide variety of information that allows students to master subjects that they don't understand in class. Second, TikTok may be utilized as an interactive learning tool since it offers engaging features that encourage students to actively participate in class. In addition, the duration of the video is quite short so that students don't get bored easily. Finally, TikTok can increase students' level of confidence in speaking English because TikTok provides various kinds of English-speaking exercises that can improve students' speaking skills and make them more confident.